Bioethanol production from palm wood using Trichoderma reesei and Kluveromyces marxianus. (January 2019) - Raja Sathendra, E.; Baskar, G.; Praveenkumar, R.; Gnansounou, Edgard
Highlights: Palm wood was pretreated using hydrothermal technique in conjunction with chemical methods. Bioethanol was produced from palm wood hydrolysate using K. marxianus MTCC 1389. Fermentation parameters were optimized using RSM and ANN. The maximum bioethanol yield of 22.90 g/l was obtained at optimum conditions. Abstract: In the present work, palm wood was pretreated using hydrothermal technique in conjunction with chemical method for removal of lignin. Pretreated palm wood was subjected to hydrolysis using Trichoderma reesei MTCC 4876. Subsequently bioethanol was produced using palm wood hydrolysate by Kluveromyces marxianus MTCC 1389. RSM was used to identify the non-linear relationship and optimize various process parameters such as parameters such as pH, temperature, agitation rate, substrate concentration and inoculum size for bioethanol production. ANN constructed with 5-2-1 topology was also used to optimize process parameters. The experimental bioethanol yield of 22.90 g/l was obtained at ANN optimum conditions of temperature 45 °C, agitation rate 156 rpm, pH 5, substrate concentration 8% (v/v) and inoculum size 3.2% (v/v).